Friction characteristics of skewed roller brakes - Oliver-Hall, Richard. (Cranfield University, 1998)
The project sponsors design and manufacture skewed roller brake devices for use in aircraft flight control actuation systems. Design tools have previously been developed to predict the torque characteristics ofthese devices. A fundamental deficiency ofthese tools is the use ofempirical friction coefficient data gathered from a limited test sample. A need was identified to develop a friction coefficient model based on the operational parameters ofthe design, namely load, speed and lubricant viscosity. The development and validation ofthis model formed the basis ofthe technical research objective. A cost benefit analysis indicated that the sponsors could reasonably expect to gain a significant technical competitive advantage over their competitors ifthe technical research objective could be achieved. This advantage should provide opportunities for premium pricing ofthe product and enhanced opportunities to enter new markets. Additionally, the sponsors could expect lead time reductions and cost savings of £69000 from the removal ofthe need to conduct prototype tests to assess the effective friction coefficient. A friction coefficient model and skewed roller torque equation design tool have been successfully developed, satisfying the technical research objective. The friction coefficient model is defined in terms of lubrication number. The lubrication number parameter incorporates lubricant viscosity, roller speed, roller load and contact surface roughness terms, fully describing the operational parameters ofa design. Experimental evidence has validated the model using two lubricants, a hydraulic fluid, Brayco 795 and a mineral oil, Catenex 79. The tests cover a lubrication number range from 2 x 10-5 to 6 X 10-2 with a mean Hertzian stress from 0.27 to 0.61 Gpa. The success ofthis project has ensured that the sponsors will reap the cost and design lead time savings predicted in the cost benefit analysis and have the tools necessary to develop new markets and premium pricing business opportunities.